Advanced Methods of Mathematical Physics - Kaushal, R S; Parashar, D (New Delhi : Narosa, 2008)
The second edition of Advanced Methods of Mathematical Physics has been considerably revised, enlarged and updated. This is typically a two-semester course material for students pursuing Master?s degree programs in theoretical physics and mathematics covering such topics as the theory of finite groups, introductory topology and differential geometry, integral equations, Sturm-Liouvilles?s theory including Green?s functions, stochastic processes and stochastic differential equations, nonlinear dynamics, solution of nonlinear differential and integral equations, symmetries of differential equations and normal modes in nonlinear dynamical systems.What the anvil means to the blacksmith, what a car means to the businessman, what a violin means to the musician, that?s what mathematics means to a theoretical
Includes Appendix A-470, B-501p; Include bibliographical references 511-513p; Index 514-519p
Keywords: Differential geometry; Integral equation; Mathematical physics; Nonlinear dynamics; General Science